Lessons learned from kidney dysfunction: Preventing organ failure - John, Stefan (Medizinische Klinik - Intensivmedizin und Notfallmedizin, 2020)
Background: Acute kidney injury (AKI) is a common and severe complication in patients in the intensive care unit with a significant impact on patient’s mortality and morbidity. Therefore renal protective therapy is very important in these severely ill patients. Aim: Several renal protective strategies have been postulated during recent decades, which came from pathophysiologic concepts and have been contradicted or changed during the last few years. So lessons had to be learned in AKI, leading to new, in many cases completely reversed preventive and therapeutic concepts which may also be important for protection in other organs. Recent findings: Most important for renal protection is the early identification of patients at risk for AKI or with acute kidney damage before renal function further deteriorates. A stage-based management of AKI comprises more general measures like discontinuation of the nephrotoxic agent but most importantly early hemodynamic stabilization. Recent research has contradicted that AKI is renal ischemia caused by vasoconstriction with consecutive tubular necrosis. In septic AKI, renal blood flow is even increased. Intrarenal vasodilation together with microcirculatory changes and redistribution of blood flow lead to a drop in glomerular filtration by functional changes. Accordingly it had to be learned that not vasodilators but vasoconstrictors are beneficial in AKI. A mean arterial blood pressure target of >65 mm Hg is often recommended but exact targets are not known, and patients with pre-existing hypertension even need higher perfusion pressure. Also the concept that fluid therapy is always beneficial for the kidney in shock states had to be revised. A volume restrictive therapy with only balanced crystalloids is also becoming more important in AKI. Still no specific pharmacological therapy for renal protection is available. Inflammation and mitochondrial dysfunction appear to play a significant role in AKI. Anti-inflammatory strategies are under investigation and may become more important for AKI prevention and therapy in the future.
CRIS-Team Scopus Importer:2020-02-25
Keywords: Acute kidney injury; Fluid therapy; Hemodynamic stabilization; Sepsis; Vasopressors